2001
DOI: 10.2307/2680207
|View full text |Cite
|
Sign up to set email alerts
|

Windstorm Disturbance without Patch Dynamics: Twelve Years of Change in a Minnesota Forest

Abstract: In an old-growth Pinus-Populus-Acer forest, treefall areas did not diverge from undisturbed control areas over a 12-yr period following windstorm disturbance. Woody plant populations sampled in 1984, 1992, and 1996 changed significantly over time, but changes in treefall areas did not differ from changes in control areas in plant species richness, composition, or vegetation structure. Preexisting tall shrubs and windfirm saplings cast heavy shade even where canopy trees blew down, preventing formation of deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 19 publications
7
36
2
Order By: Relevance
“…As similar to the stands described in Webb and Scanga (2001), delay in recovery of tall tree species after a major disturbance is common also in the region, because of the interference of dense dwarf bamboo cover to tree regeneration. The elevated soil surface is particularly important for seedlings establishments against dense dwarf bamboos in this type of mixed forests (Noguchi and Yohida 2004).…”
Section: Discussionmentioning
confidence: 73%
“…As similar to the stands described in Webb and Scanga (2001), delay in recovery of tall tree species after a major disturbance is common also in the region, because of the interference of dense dwarf bamboo cover to tree regeneration. The elevated soil surface is particularly important for seedlings establishments against dense dwarf bamboos in this type of mixed forests (Noguchi and Yohida 2004).…”
Section: Discussionmentioning
confidence: 73%
“…Only P. serotina density is presently higher than its occurrence in 1967, increasing from approximately 10 to 360 -stems ha )1 . Though numerous studies have reported canopy gaps to promote diversity enrichment (Collins and Pickett 1988;Goldblum 1997;Anderson and Leopold 2002) and additional studies report increased plant density and cover in treefall gaps as compared to the surrounding closed canopy conditions (Moore and Vankat 1986;Collins and Pickett 1988;Goldblum 1997), these trends are not always observed (Clebsch and Busing 1989;Webb and Scanga 2001;Forrester and Runkle 2000). We measured few differences between these two environments within the Sunken Forest, even though low light conditions in the forest understory created by the evergreen canopy led us to expect the vegetation would respond to increased light conditions in treefall gaps.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, five years after the storm at Kemp Station, yellow birch and white pine seedlings were common in large gaps or on tip-up mounds in partial shade (J. J. Hanson, personal observation). Successful recruitment of midtolerant tree species is sometimes prevented by dense advance regeneration or shrubs (Webb 1989, Beckage et al 2000, Webb and Scanga 2001, but the pre-storm, hemlock-dominated stands in this study did not have dense hardwood understories.…”
Section: Influence Of Moderate-intensity Storms On Canopy Conditions mentioning
confidence: 72%